Staff and student attitudes towards career education: a Western Australian study. - Dixon, Kathryn (1993)
The main purpose of the study was to investigate the attitudes of staff and students at a Western Australian metropolitan high school towards the vocational education program, by examining the factors affecting the development of those attitudes and those affecting the implementation of the program at the school. Vocational education in Western Australia is synonymous with career education in other Australian states and the term career education is used throughout this paper. With respect to the formation of attitudes towards career education, the study proposed that in the school context, influential areas were significant others, past experiences, individual personalities and information. The research is descriptive in nature. The staff and students were asked to complete a questionnaire and were formally interviewed. A measure of the non verbal behaviour of staff and students during the interviews was also undertaken using a five point scale from negative to positive. The sample consisted of 14 staff and 240 students. The main findings of the study showed that the majority of the staff and students had developed negative attitudes towards career education. They believed the course lacked rigour and that significant others such as peers, parents, students and the Western Australian Ministry of education did not esteem career education. No needs analysis had been conducted prior to the introduction of the course in the school and staff were given no choice as to their involvement in teaching the units. Staff believed they were inadequately trained in the career education area and this led to low levels of confidence in teaching the course.